WORK-RELATED CORONARY RISK FACTORS IN REFUGEES AND MIGRANTS SETTLED IN SUMGAIT CITY - F. N. Kasumova (Российский кардиологический журнал)
This cross-sectional population study of the prevalence of coronary heart disease (CHD) and major coronary risk factors, in regard to work type, was performed among male refugees and migrants settled in Sumgait City (n=865; age 20-59 years). The prevalence of coronary risk factors was generally higher in non-working individuals and non-manual workers. The highest prevalence of Stage I obesity (36,4±8,4%), hypercholesterolemia (36,4±14,5%), hypertriglyceridemia (72,7±13,4%), and dyslipidemia was observed in the age group IV, among non-manual workers. The highest prevalence of low physical activity (83,0±4,%), arterial hypertension (77,8±3,7%), and hypo-α-cholesterolemia (31,3±8,2%) were also registered in the age group IV, but among non-working participants. Therefore, our results not only confirm the association between the prevalence of major coronary risk factors and work type among refugees and migrants residing in Sumgait City, but also point to the need for primary preventive interventions in this population.